2020
DOI: 10.21449/ijate.623080
|View full text |Cite
|
Sign up to set email alerts
|

Using the Malmquist Index in Evaluation Process to Enhance Mathematical Literacy in High School Students

Abstract: The study aimed to calculate the evaluation of 9 th grade female students and compare the development of the educational process in increasing mathematical literacy using the Malmquist Index at different time intervals. This educational process was accomplished by analysing and integrating realistic mathematical education and mathematical problem-solving. The populations of the study were 120 ninth grade female students. Each student was as a DMU whose inputs were the math test score and the outputs were math … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Curiously, some of the intervention studies that did not draw on any particular theory included learning and the acquisition of knowledge on specific STEM content. For instance, the study by Tarng et al ( 2011 ) provided the basic concepts of synchrotron light sources, while other interventions focused on students' attitudes and interest in STEM subjects and careers (Christensen et al, 2014 , 2015 ; Christensen and Knezek, 2017 ; Acuña et al, 2018 ) or STEM performance (Brown and Brown, 2019 ; Jordaan and Tavenga, 2019 ; Mostoli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, some of the intervention studies that did not draw on any particular theory included learning and the acquisition of knowledge on specific STEM content. For instance, the study by Tarng et al ( 2011 ) provided the basic concepts of synchrotron light sources, while other interventions focused on students' attitudes and interest in STEM subjects and careers (Christensen et al, 2014 , 2015 ; Christensen and Knezek, 2017 ; Acuña et al, 2018 ) or STEM performance (Brown and Brown, 2019 ; Jordaan and Tavenga, 2019 ; Mostoli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, some of the intervention studies that did not draw on any particular theory included learning and the acquisition of knowledge on specific STEM content. For instance, the study by (Christensen et al, 2014(Christensen et al, , 2015Christensen and Knezek, 2017;Acuña et al, 2018) or STEM performance (Brown and Brown, 2019;Jordaan and Tavenga, 2019;Mostoli et al, 2019).…”
Section: Rq Methodology Of the Interventionsmentioning
confidence: 99%
“…The results of [18] research said that system user satisfaction is positively related to access speed. Research conducted by [19], [20] and [21] showed different results, where they said that access speed had no effect on system usage activities.…”
Section: Number Of Users Accessing the Server Concurrentlymentioning
confidence: 99%
“…35 For instance, going with the proliferation of low self-efficacy being the single most important factor affecting females' enrolment in STEM, Oinas-kukkonen and Harjumaa This study argues that it is imperative to consider the broader social context of this issue by looking at the sociocultural context surrounding female students. 42 This is because studies that investigate the factors that hinder females' participation in STEM fields 43,41 point to factors that revolve around a wide variety of areas such as school, 42 family, 43 culture 46 and individual characteristics 43,44,45 Factors such as STEM curriculum, 47 the absence of female STEM teachers 48 and weak government policies 49 are the most cited school factors that discourage females' participation in STEM fields, while parents line of work 50 is the most cited family factor. Concerning cultural factors, societal gender role belief that makes people feel that certain activities are more efficiently accomplished by one gender as compared to the other 46,51 was reported to significantly influence females' participation in STEM fields, while low selfefficacy 52 in STEM subjects, lack of social belonging in STEM fields, 53 lack of interest 54 and lack of career-driven 55 goals are the major individual factors.…”
Section: Literature Reviewmentioning
confidence: 99%